Pemberdayaan Ekonomi Kelompok Masyarakat Sadar Wisata Kawasan Mandeh Bahari melalui Program Pelatihan ESP Bahasa Inggris Pariwisata di Kabupaten Pesisir Selatan - Ratmanida Ratmanida; Muhammad Al Hafizh; Rusdi Noor Rosa (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2020)
The existence of Kelompok Sadar Wisata (Pokdarwis)  will give benefit to the the district government and the participating communities will also be helped because there are open business opportunities that can improve the family economy. So that this business opportunity can be optimized it is necessary to provide guidance and provision of soft skills and life skills for Pokdarwis. But the problem is that Pokdarwis has not been managed to its full potential, it can be seen from the still weak supporting skills needed by Pokdarwis in carrying out its roles and functions. One of the important and urgent skills to be trained in is English tourism skills and web management skills for tourism promotion. Solutions offered to increase productivity and involvement of the local community to manage the tourism industry are through improving English language skills for Pokdarwis through English ESP training for tourism and training in making and managing tourism promotion web. The partner chosen for this activity was Pokdarwis Mandeh Bahari Area, Koto XI Tarusan District, South Pesisir Regency.